Studies in the relationship of health status to socio economic factors and health resources in Sri Lanka. - Jayasuriya, A..R (My University, 1993)
This study attempts to find relationships between health status and socio-economic factors that influence health levels. Another objective was to assess the relative importance of socio -economic factors and health resources on health status. Variables measuring the socioeconomic factors and health resources available were identified. Their relationships to health status indicators were studied using the areas of superintendent of health services (Health districts) as the unit of analysis. These areas were chosen as they conform to the drainage areas for health care and overcomes to some extent the error of deaths being registered by place of death and not the place of residence. The findings of the study show that in general the health status indicators have a closer relationship to socio-economic indicators than health resource indicators. It was identified that 'micro' level studies to untangle some of the inter relationships between health status and its determinants are to be measured